Enhancement of dewatering properties of Kaolin suspension by using Cationic Polyacrylamide (PAM-C) Flocculant and Surfactants - Hussain, Jabir; Jami, Mohammed Saedi; Muyibi, Suleyman Aremu (INSI Publications, 2012)
This paper reports the results on enhancement of dewaterability of sludge using kaolin synthetic sludge as model material by addition of cationic polyacylamide (PAM-C) in the presence of surfactants which are anionic sodium dodecyl sulphate (SDS) and non-ionic Triton X-100. In this study, kaolin synthetic sludge was used as model material as it has similar property of being very difficult to dewater like wastewater treatment plant sludge. Previous study reported that simultaneous addition of PAMC to the surfactants decreased the settling rate and also helped to reduce the moisture content substantially. However, the flocs formed show better filtration and dewatering behavior in terms of reduction in specific cake resistance to filtration (SRF) and cake moisture content. In this study, the kaolin synthetic sludge dewaterability was enhanced by addition of flocculant and surfactant. The results of different concentration of PAM-C – SDS combinations used were compared and optimized. Sludge dewaterability was expressed in terms of settling rate and specific resistant of cake to filtration (SRF) for various concentration and combination of dewatering aids. The settling rate obtained for PAMC as an optimum dosage of 1mg/g. The settling rate of kaolin suspension could be improved up to 10-times by flocculation of kaolin with flocculants and surfactants.